KEANEKARAGAMAN NEMATODA DALAM TANAH PADA BERBAGAI TIPE TATAGUNA LAHAN DI ASB-BENCHMARK AREA WAY KANAN - I Gede Swibawa (Universitas Lampung, 2001)
The soil nematode diversity in several land-use types in Way Kanan ASB-Benchmark Area. The conversion of forest to intensive agroecosystem such as monoculture system reduces biodiversity of the plant, herbivore, and decomposer subsystems. Those changes affected the litter and plant root quality. Consequently, few soil nematode species could be dominant and cause of disturbance of the stability of the below ground community. The increasing populations of plant parasitic nematodes usually occur on monoculture system . The research was conducted to study the effect of forest changes in several land use types on soil nematode diversity in Way Kanan Benchmark Area. Soil sampling on five land use types (secondary forest, agroforest or tree based agriculture, plantation, cassava field, and Imperata grass land) was conducted in November1996 and December 1997. Nematodes were extracted by decantation-centrifugation with sugar method. The soil nematodes were grouped into order and generic level including plant parasitic and non- parasitic. The results show that the order of Rhabditida, Dorylaimida, and Tylenchida were found from those five land-use types. The total genera of plant parasitic nematodes in Imperata grass land were the highest among the other four land use types. The total number of non-plant parasitic nematodes in secondary forest (28.0 individual per 300 cc of soil) was higher than total number in the plantation ( 2.6 individual per 300 cc of soil), cassava field (4.0 individual per 300 cc of soil) or Imperata grass land (6.6 individual per 300 cc of soil). The total number of plant parasitic nematodes in Imperata grass land (59.8 individual per 300 cc of soil), agroforest (59.0 individual per 300 cc of soil), secondary forest (48.2 individual per 300 cc of soil), and plantation (17.6 individual per 300 cc of soil) were not significantly different, but total number in Imperata grass land and agroforest were significantly higher than that in cassava field (11,6 individual per 300 cc of soil).